2014
DOI: 10.1155/2014/896206
|View full text |Cite
|
Sign up to set email alerts
|

Competing Endogenous RNA: The Key to Posttranscriptional Regulation

Abstract: Competing endogenous RNA, ceRNA, vie with messenger RNAs (mRNAs) for microRNAs (miRNAs) with shared miRNAs responses elements (MREs) and act as modulator of miRNA by influencing the available level of miRNA. It has recently been discovered that, apart from protein-coding ceRNAs, pseudogenes, long noncoding RNAs (lncRNAs), and circular RNAs act as miRNA “sponges” by sharing common MRE, inhibiting normal miRNA targeting activity on mRNA. These MRE sharing elements form the posttranscriptional ceRNA network to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
221
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(233 citation statements)
references
References 31 publications
3
221
0
Order By: Relevance
“…Emerging evidence suggests that lncRNAs act as endogenous miRNA sponges to bind to miRNAs and regulate their function [26,27]. To find out whether TUG1 serves as a miRNA sponge, we performed the bioinformatics analysis and found that TUG1 contained binding sites for several miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that lncRNAs act as endogenous miRNA sponges to bind to miRNAs and regulate their function [26,27]. To find out whether TUG1 serves as a miRNA sponge, we performed the bioinformatics analysis and found that TUG1 contained binding sites for several miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Noncoding RNAs (ncRNAs), small (<200 kb) and long (lncRNAs) (>200 kb), have attained extensive attention recently as the new crucial biological regulators from nuclear organization to epigenetic modification of posttranscriptional regulation and RNA splicing (Gupta et al, 2010;Tsai et al, 2010;Ma et al, 2012;Sen et al, 2014). Moreover, functional analyses have revealed that lncRNAs play essential roles in a range of developmental processes , SuNing Huang 1 , Gang Chen 2 * and diseases, including tumorigenesis and metastasis (Gupta et al, 2010;Cao, 2014;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence gathered from numerous studies highlights the significance of miRNAs as being vital in the regulation of numerous physiological processes such as cell proliferation, differentiation and apoptosis (16)(17)(18). Both the MTT and colony formation assays demonstrated that miR-219-5p significantly suppressed the growth and proliferation of CRC cells in vitro.…”
Section: Discussionmentioning
confidence: 99%